Pulmonary Arterial Hypertension - Chin, Kelly M.; Rubin, Lewis J. (Journal of the American College of Cardiology, 2008)
Pulmonary Arterial Hypertension Kelly M. Chin, Lewis J. Rubin Significant advances in the treatment of pulmonary arterial hypertension have occurred over the last 10 years, starting with the approval of epoprostenol in 1998, followed by the development of subcutaneous and inhaled prostacyclins, oral endothelin antagonists, and oral phosphodiesterase type-5 inhibitors. Combination therapy is more frequently being used, and limited data on novel therapies such as stem cell transplantation have been published. The purpose of this review is to describe the current state of evidence for the diagnosis, prognosis, and treatment of the patient with pulmonary arterial hypertension. Significant advances in the treatment of pulmonary arterial hypertension (PAH) have occurred over the last 10 years, starting with the approval of epoprostenol in 1998. Subsequently, multiple additional medications have received approval, including a subcutaneous prostacyclin, an inhaled prostacyclin, and oral medications in 2 separate classes. Over this same period, the classification of pulmonary hypertension has been revised with changes including the substitution of the term idiopathic for primary PAH and an expanded list of conditions felt to be associated with the development of PAH. Long-term follow-up studies have provided better information on prognosis and expected outcomes with treatment, with particularly valuable data on reassessment of prognosis after treatment with epoprostenol. Combination therapy is more frequently being used, and limited data on novel therapies such as stem cell transplantation have been published. The purpose of this review is to describe the current state of evidence for the diagnosis, prognosis, and treatment of the patient with PAH.